PENGEMBANGAN MEDIA PEMBELAJARAN KOMIK DIGITAL BERBASIS APLIKASI PIXTON UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN PESERTA DIDIK DI KELAS III SEKOLAH DASAR - Nurkhalifatun Nisa; Indhira Asih Vivi Yandari; Reksa Adya Pribadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to develop a digital comic-based learning medium using thePixton application to improve the understanding of multiplication as repeatedaddition among third-grade elementary school students. The research methodused is the ADDIE development model, which includes Analysis, Design,Development, Implementation, and Evaluation. The Pixton-based digital comicwas validated by a team of experts and teachers before being implemented withthe research subjects, namely third-grade students of SDN Kaloran. The validationtest of the Pixton-based digital comic product received an average scorepercentage of 82% from the expert team, categorized as